PENGARUH KELOMPOK REFERENSI DAN BUDAYA TERHADAP KEPUTUSAN MENJADI ANGGOTA SANGGAR TARI - Elvira Pradipta Sutiana; Risha Fatikha Sari; Ajat Sudrajat (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
"The Influence of Reference Groups and Culture on the Decision to Become Members of the Dance Studio" under the guidance of Ajat Sudrajat, SE., MM. The consumer behaviour in making purchasing decisions can be influenced by three factors including internal factors, external factors, and the decision-making process. The study entitled "The Influence of Reference Group and Culture on the Decision to Become a Member of the Dance Studio aims to analyze the influence of X1 and X2 on Y" has a population of 329 people and a sample of 100 people. By using a quantitative approach and descriptive analysis, in the variable X1 the dimension of value expression obtained the highest average score with a percentage of 51.82%, in the X2 variable the highest was the view of 59.50%, in the variable Y the highest was personality at 25.57%. Whereas in the verification analysis, the relationship between X1 and X2 is 0.426 which means that the correlation is moderate. For 5% error the two-tailed test and df = n - 3 = 97 is 1.66071. Because the t statistic> from t table (4.328> 1.66071), Ho is rejected. The significant column number is 0.000 or the probability is far below 0.05. So it means that X1 and X2 partially have a significant effect on Y.From the ANOVA test or F test, it is found that the F count is 19.714 with a significant level indicating a value of 0.000 which means less than 5%, it can be concluded that X1 and X2 are Simultaneously affects Decision Y. Keywords : Reference Group, Culture, Purchasing Decision